Analisis HOTS Pada Tes Tertulis Dalam Bentuk Objektif Dan Uraian Pendidikan Dasar - Fia Alifah Putri; Namiroh Lubis; Nurzakiah Simangunsong; Maulida Rizqia; Mikyal Hardiyati (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The importance of the thinking process dimension in Bloom's Taxonomy which has been revised by Krathwohl and Anderson in the realm of providing material and assessments carried out in the realm of knowledge which consists of the abilities: remembering (remembering-C1), understanding (understanding-C2), applying (applying-C3) , analyzing (analyzing-C4), evaluating (evaluating-C5), and creating (creating-C6). HOTS questions generally measure abilities in the domains of analyzing (analyzing-C4), evaluating (evaluating-C5), and creating (creating-C6). This article generally aims to describe the use of HOTS (High Order Thinking Skills) in objective test questions and descriptions. The method used is the library research method. The author collected a number of references in accordance with the analysis of the assessment of HOTS questions on written tests in objective form and descriptions of both journals, books and related government regulatory documents. The results of this research show that analysis of the assessment of HOTS questions on written tests in objective and descriptive form can improve the critical, logical, reflective, metacognitive and creative thinking skills that school students must have as early as possible or at elementary school level.